Rilkean Memory. (September 2015) - Rowlands, Mark
Abstract: This paper identifies a form of remembering sufficiently overlooked that it has not yet been dignified with a name. I shall christen it Rilkean Memory. This form of memory is, typically, embodied and embedded. It is a form of involuntary, autobiographical memory that is neither implicit nor explicit, neither declarative nor procedural, neither episodic nor semantic, and not Freudian. While a discussion of the importance of Rilkean memory lies beyond the scope of this paper, I shall try to show that admitting Rilkean memory into our ontology does point us in the direction of a very different conception of the mind and mental processes.